Quality and Value Relevance of Financial Statements: Improving Sustainability Reporting - Anna, Yane Devi; Rinining, Dita Raridwi (Universitas Pendidikan Indonesia, 2021)
The aim of this study was to examine the effect of the quality of financial statements and the value of relevance in financial statements on Sustainability Reporting. The study was conducted on winner companies based on categories from the National Center for Sustainability Reporting and the Indonesia Stock Exchange listed organizations between the years 2016 - 2018. Analysis of research using partial least square. The results showed that financial reporting quality which is proxied by conservatism accounting has an effect on sustainability reporting on social and environmental aspects, while on economic aspects it has no effect. Value relevance of financial statement using earnings per share on sustainability reporting, value relevance of financial statements using book value per share has no effect on aspects of social performance of sustainability reporting.